The firm relocation decision: a logit model - Aleid Brouwer; Ilaria Mariotti; Jos van Ommeren (European Regional Science Association (ERSA), 2002)
This paper deals with the relocation of firms. There are indications from former research, that age, size and market are determinants of relocated companies. This paper aims to demonstrate that mobile firms are younger, more export oriented and more rapidly growing. With the use of two theories, Location theory and the theory of Organisational Ecology, it is tried to construct a theoretical background for an age-related bias in the decision to relocate. Location theorieexplain from different perspectives the location of economic activities. Spatial movements of firms represent only a small part of industrial change, but it does influence the overall change of production and employment levels. Organisational Ecology deals with the causes of vital events (birth, death and mobility) of firms in the organisational population, because mobility is one of the visible outcomes of the selection process. The theoretical constructs for this decision are tested with the use of the Cranet database that provides information on company relocation in eighteen European countries in 1996-1999. First, a general analysis of the phenomenon in the European countries is presented. Second, the connection between relocation and age, size and market of companies in three example countries (Italy, the Netherlands and the United Kingdom) is described on the basis of the literary review. The findings are in general that when firms grow older they are too large and too embedded in the spatial environment to move. Younger firms are more likely to relocate, because they are expected to have higher growth rates and therefore need more space, one incentive to relocate.
Keywords: 330